Evaluation of photobiomodulation therapy for genitourinary syndrome of menopause: A single-center prospective study - Pei-Chi Wu; Ho-Hsiung Lin; Chi-Hau Chen; Yih-Shing Kuo (PLoS ONE, 2026)
Background Genitourinary syndrome of menopause (GSM) is common, and non-hormonal treatment options are needed for women unsuitable for or reluctant to use estrogen therapy. Objective To prospectively evaluate clinical outcomes and clinical improvement rates of photobiomodulation (PBM) for GSM. Methods Twenty-seven postmenopausal women with GSM were enrolled in a prospective study conducted from January 2024 to July 2025. Participants received eight weekly 30-minute sessions of pulsed 660-nm PBM delivered through a stationary silicone vaginal light-guide probe. With the probe attached, target irradiance was 32.38mW/cm² at the probe tip and 13.38mW/cm² at the probe side, corresponding to per-session radiant exposures of 29.14J/cm² at the vaginal fornix and 12.04J/cm² at the vaginal wall. Assessments occurred at baseline (V1), pre-4th session (V2), pre-8th session (V3), and three months post-treatment (V4). The primary outcome was the Vaginal Health Index (VHI). Secondary outcomes included validated questionnaires for lower urinary tract symptoms (LUTS) and sexual function (FSFI). Clinical improvement was defined using established minimal clinically important differences (MCID), minimal detectable change (MDC), and cutoff scores as thresholds. Results The mean age of participants was 62.9 ± 9.7 years. Total VHI scores were significantly higher at all follow-up time points compared to baseline ( p < 0.05), with all participants reaching the non-atrophic VHI threshold at V4. UDI-6, IIQ-7, OABSS, and several KHQ domains improved significantly ( p < 0.05) and persisted through the 3-month follow-up. Total FSFI scores improved significantly (p < 0.05), but only 13.3% reached the clinical cutoff (≥26.5) at V4 for functional recovery. No adverse events were observed during the study period. Conclusions Intravaginal 660-nm PBM is a well-tolerated, non-hormonal modality that may improve objective vaginal health and subjective symptoms in GSM. As an integrated therapeutic option, PBM may also improve GSM-related LUTS, suggesting potential relevance for geriatric patients with polypharmacy concerns. Trial registration ClinicalTrials.gov NCT06074120